Les motifs hellénistiques dans le poème de Léon le Philosophe «Job» - SÉNINA (Nonne Kassia), Tatiana (Byzantina Symmeikta, 2019)
In his poem “Job” Leo the Philosopher mentions as models for imitation not only Job but also philosophers, poets and other historic personalities. The abundance of Hellenistic allusions in the poem makes a strong feeling that this piece of work was created for people whose mind is more used to Hellenistic rather than Christian cultural symbols. Speaking of virtues, Leo clearly prefers to take examples from the life of ancient philosophers. Plato and the Stoics are for him the teachers of virtue, and he places Socrates among the “people of a high divine life” along with Christian saints. Although the poem makes plenty of appeals to bear grief and poverty, in the end the author asks God not to send too much suffering to anyone but give a chance to lead an undisturbed life, enjoying “some of riches and properties.” In general, Leo in his poem appears more like a humanist and Hellenist, than as a Christian traditionalist.